High‐Accuracy Photoplethysmography Array Using Near‐Infrared Organic Photodiodes with Ultralow Dark Current. Issue 10 (16th March 2020) - Simone, Giulio; Tordera, Daniel; Delvitto, Ezequiel; Peeters, Bart; van Breemen, Albert J. J. M.; Meskers, Stefan C. J.; Janssen, René A. J.; Gelinck, Gerwin H.
Abstract: Reflectance oximeters based on organic photodiode (OPD) arrays offer the potential to map blood pulsation and oxygenation via photoplethysmography (PPG) over a large area and beyond the traditional sensing locations. Here, an organic reflectance PPG array based on 16 × 16 OPD pixels is developed. The individual pixels exhibit near‐infrared sensitivity up to ≈950 nm and low dark current density in the order of 10 −6 mA cm −2 . This results in high‐quality PPG signals. Analysis of the full PPG waveform yields insight on the artery stiffness and the quality of blood circulation, demonstrating the potential of these arrays beyond pulse oximetry and heart‐rate calculation. Abstract : A reflectance oximeter array based on 16 × 16 organic photodiodes (OPDs) is presented. The OPD pixels exhibit near‐infrared sensitivity and ultralow dark current. The OPD array records state‐of‐the‐art photoplethysmography (PPG) waveform signals over a large area, providing information on artery stiffness and blood circulation in addition to vital sign parameters such as heart beat and blood oxygen saturation (SpO2 ).